Continuance usage intention and its antecedents on using OVO e-wallet application in Denpasar - Darmiasih, Made; Setiawan, Putu Yudi (International research journal of management, IT and social sciences, 2020)
This study aims to explain the effect of information quality, perceived privacy protection, perceived security protection on trust, and its effect on continuance intention to use OVO in Denpasar. This research was conducted in Denpasar, using 139 respondents. This study uses Structural Equation Modelling (SEM) analysis techniques with the Partial Least Square approach. This study shows that information quality has a positive and significant effect on trust. Perceived privacy protection has a positive and significant effect on trust and continuance usage intention. Perceived security protection has a positive and significant effect on trust and continuance usage intention. Also, this study also shows that trust has a positive and significant effect on continuance usage intention. Information quality was found that have no significant effect on the continuance usage intention.